The role of amphiphilic chitosan in hybrid nanocellulose–reinforced polylactic acid biocomposite. (5th May 2021) - Nasution, H.; Olaiya, Niyi G.; Haafiz, M. K. Mohamad; Abdullah, C. K.; Bakar, Suriani Abu; Olaiya, Funmilayo G.; Mohamed, Azmi; H. P. S., Abdul Khalil
Abstract: The blending of hydrophilic materials with hydrophobic polymers has been reported with agglomeration due to their functional group immiscibility properties. In this study, the properties of PLA/CNF biocomposite were enhanced with amphiphilic chitosan produced by a substitution reaction. The substitution reaction was studied with FT‐IR analysis. The amphiphilic chitosan was used as part of the matrix PLA/chitosan and reinforced with CNF to obtain PLA/chitosan/CNF biocomposite using combined melt extrusion and compression molding technique. The morphology and structural bonding of amphiphilic chitosan added in the biocomposite were studied with SEM, XRD, and FT‐IR. Furthermore, the mechanical, thermal, and wettability properties of PLA/chitosan/CNF composite were studied with tensile analysis, thermogravimetry analysis, differential scanning calorimetry, water absorption, thickness swelling, and contact angle test. The preparation of the amphiphilic chitosan was successful, as observed from the FT‐IR functional group analysis. The PLA/chitosan/CNF biocomposite properties showed a significant enhancement in the miscibility, mechanical, and thermal properties with no agglomeration. The wettability test also showed that the composite has a reduced hydrophobic nature compared with the neat PLA. The PLA/chitosan/CNF properties showed potential use for packaging application.